Identifying the impact of stakeholder and top management support on shaping environmental innovation, green product development, and environmental performance in Brazil and Portugal's plastics industry - Marcelo Curth; Alzira Maria Ascensão Marques; Ítalo José de Medeiros Dantas (Revista de Ciências da Administração : RCA)
Goal: This paper aims to identify the influence of stakeholders and top management support on environmental innovation strategy, green product innovation, and environmental performance in the context of the plastics industry of Brazil and Portugal.